Spectral Behavior of Irradiated Sodium Chloride Crystals Under Europa‐Like Conditions. Issue 12 (12th December 2017) - Poston, Michael J.; Carlson, Robert W.; Hand, Kevin P.
Abstract: F‐ and M‐color center formation (decay) was observed during (after) irradiation of sodium chloride crystal grains with 10 keV electrons as a function of temperature, radiation dose rate, and radiation dose. The F centers (peak center: 460 nm) were found to form and decay at a faster rate than the M centers (peak center: 720 nm). These effects were influenced by temperature and possibly by irradiation dose rate. Tracking the band depth ratio of the color center features during irradiation could enable age determination of geologically very young features on the surface of Europa and other icy ocean worlds. Plain Language Summary: Does Jupiter's moon Europa have the right conditions for life? Europa is thought to have a sub‐surface ocean of salty water. Sodium chloride at the surface is a likely sign of mixing between the surface and the sub‐surface ocean. Such mixing would increase the likelihood of the sub‐surface ocean supporting microbial life. Finding former ocean material very recently arrived at the surface would provide the best understanding of the ocean (short of directly sampling it). We performed experiments examining how sodium chloride visible light absorption changes in a simulated Europa surface environment. We found that by calculating the ratio of two main absorption features, called "color centers", it is possible to determine the time since the sodium chloride arrived at the surface, up to twenty years at Europa. Key Points: F‐ and M‐center formation in NaCl under electron irradiation was found to be in dynamic equilibrium dependent on temperature and possibly dose rate The ratio of M‐/F‐center band depth was found to be largely independent of irradiation dose rate and temperature M‐/F‐band depth ratio enables spectroscopic surface exposure age estimation for NaCl exposures with known irradiation dose rate